Exploring the Potential to Repurpose Flexible Moulded Polyurethane Foams as Acoustic Insulators - Mester Enikő; Pecsmány Dániel; Jálics Károly; Filep Ádám; Varga Miklós; Gráczer Kitti; Viskolcz Béla; Fiser Béla; Bela Fiser; Фішер Бейло (MDPI, 2022)
Abstract. Polyurethane flexible foams are widely used for a variety of applications to improve comfort and durability. Their long-term frequent use inevitably leads to the generation of waste that needs to be treated. The recycling and reuse of polyurethane waste are essential to achieve an environmentally friendly economy. The present study investigates the potential to reuse and repurpose flexible polyurethane foam from automotive seat cushion waste materials. Flexible foams were prepared with different hardnesses using isocyanate–polyol ratios between 0.8 and 1.2 NCO-index. Dry heat aging tests were performed to mimic the long-term usage of the materials. The decrease in compressive strength was compared with the change in acoustic damping properties before and after the aging tests using an acoustic tube, and the change in foam cell structures was also analyzed by micro-CT. On the basis of the results obtained, although the foam systems are no longer suitable to be used as seat cushions due to aging, they can still be used as sound insulation materials within a given frequency range, as their sound absorption capacity is suitable for such purpose.
Editorial Board: https://www.mdpi.com/journal/polymers/editors
Contents: https://www.mdpi.com/2073-4360/14/1
Keywords: polyurethane repurposing; flexible foam; compressive strength; sound insulation; waste utilization